2022
DOI: 10.3389/fendo.2022.920541
|View full text |Cite
|
Sign up to set email alerts
|

Basal insulin intensification with GLP-1RA and dual GIP and GLP-1RA in patients with uncontrolled type 2 diabetes mellitus: A rapid review of randomized controlled trials and meta-analysis

Abstract: Tirzepatide, a dual agonist of Glucose-Dependent Insulinotropic Polypeptide (GIP) and Glucagon-Like Peptide 1 (GLP-1) receptors, improved glucose control and reduced body weight in different therapeutic approaches. Herein, we overviewed the role of GIP and GLP-1 in the pathophysiology of type 2 diabetes and systematically reviewed the efficacy and safety of injectable incretin-based therapy added to basal insulin in light of the results of the SURPASS-5 trial. We identified eleven randomized clinical trials. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…GLP-1RAs also provide cardiovascular and renal protection. As GLP-1RAs work efficaciously and safely, the prescription of this class of medications has gained success in T2D, even compared to other equally potent but more expensive and composite regimens, such as insulin therapy [ 177 , 178 , 179 ]. GLP-1RAs are expected to affect body composition significantly.…”
Section: Preventing Sarcopenia: a Therapeutic Target In Primary And S...mentioning
confidence: 99%
“…GLP-1RAs also provide cardiovascular and renal protection. As GLP-1RAs work efficaciously and safely, the prescription of this class of medications has gained success in T2D, even compared to other equally potent but more expensive and composite regimens, such as insulin therapy [ 177 , 178 , 179 ]. GLP-1RAs are expected to affect body composition significantly.…”
Section: Preventing Sarcopenia: a Therapeutic Target In Primary And S...mentioning
confidence: 99%
“…Compared to GLP-1RAs, TZP reduces body weight from −1.68 kg to −7.16 kg depending on the dose (5 to 15 mg, respectively) [14]. Compared to basal insulin alone rigorously titrated using a treat-to-target approach, TZP added onto basal-insulin results in the best strategy to improve the study outcome with a composite endpoint of improved glucose control and weight loss [19]. The SURPASS-6 found similar results, in which TZP in add-on to insulin glargine U100 reduced body weight by 9 kg in mean (versus weight gain in basal-bolus users: +3.2 kg) [15].…”
Section: Tirzepatide and Body Weightmentioning
confidence: 99%
“…Besides, the cardiovascular safety of other GLP-1 RAs was investigated in comparison to placebo in large prospective, randomized clinical studies; and either neutral effects or decreases in cardiovascular events have been observed [46]. Liraglutide, semaglutide (subcutaneous or oral), or dulaglutide did not differ from placebo in their respective cardiovascular outcome trials when HF was taken into account as an endpoint in its own right [9,22,23,36,38].…”
Section: Cardiovascular Outcomesmentioning
confidence: 99%